SOCIAL MEDIA ETHICS FROM A QUR'ANIC PERSPECTIVE AND ITS RELEVANCE TO THE PHENOMENON OF HATE SPEECH ON SOCIAL MEDIA - Masrufah; Moh. Zahid; Mohammad Thoha (Academic Bright Collaboration, 2026)
This study aims to examine the principles of social media communication ethics in the Qurʻan and their relevance to the phenomenon of hate speech in digital spaces. Its primary contribution lies in the reconstruction of Qurʻanic moral values through Fazlur Rahman’s double movement approach in order to construct a contextual and operationally applicable Qurʻan-based social media ethics, thereby distinguishing it from existing normative studies. This research employs a qualitative method with a library research approach. The study applies thematic interpretation (tafsīr maudhū‘ī) combined with Fazlur Rahman’s double movement hermeneutical approach to analyze Qur’anic verses related to communication ethics, particularly Q.S. al-Hujurat (49:11–12; 49:6) and Q.S. al-Ahzab (33:70). Through the first movement, the three verses are shown to respond to distinct socio-historical contexts: Q.S. al-Hujurat 11–12 addresses the culture of inter-tribal mockery and verbal degradation in pre-Islamic Arabia; Q.S. al-Hujurat 6 responds to a crisis of information validity caused by an inaccurate report; and Q.S. al-Ahzab 70 constitutes a universal command for communicative integrity. Through the second movement, each verse yields universal moral ideals that remain contextually relevant: the prohibitions of sukhriyah, lamz, tanabuz, suʻudzan, tajassus, and ghibah map precisely onto the phenomena of cyberbullying, body shaming, digital gossip, and trial by netizen; the principle of tabayyun functions as a preventive mechanism against hoaxes and disinformation; and qaulan sadidan establishes the standard for integrity in digital communication. The analysis further affirms that hate speech, hoaxes, and ghibah, while overlapping, are conceptually distinct phenomena requiring differentiated ethical responses. This study is limited to textual and contextual analyses of Qur’anic verses through a thematic interpretative approach. Therefore, further empirical research is needed to examine the implementation of Qur’anic communication ethics within contemporary digital society. This study contributes to the development of Qur’an-based digital communication ethics by contextualizing Qur’anic moral values through Fazlur Rahman’s double movement approach in responding to the phenomenon of hate speech on social media.